Prevalence and covariates of problematic gambling among a US military cohort - Gallaway, M. Shayne (Addict Behav, 2019)
The availability of and participation in gambling has increased substantially the past several decades, however studies of military members’ gambling behaviors are limited. The present study aimed to investigate potential problematic gambling and its association with demographics and behavioral characteristics in a US military cohort. We analyzed cohort data from a telephone survey during 2015–2016 of 1553 Ohio Army National Guard members. We assessed potential problematic gambling by using the 3-item National Opinion Research Center Diagnostic Screen—Loss of Control, Lying, and Preoccupation Screen (NODS-CLiP). Potential correlates examined were demographics, depression, suicidal ideation, smoking status, alcohol use, legal and financial problems, perceived general health status, pain, and impulsivity. Results indicated past-year frequent gambling (at least once per week) and lifetime potential problematic gambling was reported by 13% and 8% of respondents, respectively. Problematic gambling and past-year gambling behaviors were associated in a dose-response relationship from 18% among soldiers gambling once per week to 44% among those gambling 4 or more times per week. Correlates of screening positive for potential problematic gambling included the following: being male, currently unmarried, having left the Guard or retired, minor depression, alcohol dependence, legal problems, and increased pain. Given the higher prevalence of frequent gambling in this military cohort (8%), nearly twice the US prevalence (5%), and the association with negative psychological and behavioral outcomes, routine screening of gambling frequency and problem gambling may be needed to ensure military and veteran populations live the healthiest lives possible.